Clinico-Haematological Profile and Outcome of Dengue Fever Cas-es Admitted In 2014 at Tertiary Care Hospital, Rajkot, Gujarat - Jasmin R Oza; Bhavesh R Kanabar; Umed V Patel; Kshama Gajera; Dhara V Thakrar; Ashutosh D Jogia (Medsci Publications, 2017)
Background: Dengue fever (DF) and its severe forms - Dengue haemorrhagic fever (DHF) and Dengue shock syndrome (DSS) have emerged as a notable public health problem in terms of the mortality and morbidity associated with it. Objective: To study the clinical-haematological profile and outcome of Dengue fever cases. Methodology: A cross-sectional prospective study was conducted at PDU Government Medical College, Rajkot during 1st January to 31st December, 2014. All confirmed Dengue cases admitted in this institute during 2014 were included in the study. Analysis was done using the Microsoft Office Excel 2007 and appropriate statistical tests were applied. Results: Among 145 patients,  included in this study, 62% patients were males and 69% patients were in the age group 15-44 yrs. Fever was present in all the cases i.e. (100%), followed by myalgia(99%), headache(96%), vomiting(78%) and epistaxis(63%). Majority of the cases presented with classical dengue fever i.e.(90%) followed by DHF(10%). No death due to dengue was reported during study period. Conclusion: The most common age group for dengue fever was 15-44 yrs. Most of the patients were male. Fever was present in all the cases. No death due to dengue was reported during study period.